Juridical Analysis of the Regulations on the Use of Cannabis for Medical Purposes in Indonesia (A Comparative Study with Thailand) - Anak Agung Gede Triyatna; Putu Eka Trisna Dewi; Cokorde Istri Dian Laksmi Dewi (Jurnal Hukum Prasada, 2024)
Narcotics are substances whose use is prohibited. They have both negative and positive effects on health. Indonesian law regulates narcotics in Law Number 35 of 2009 on Narcotics, which classifies them into two categories: plant-based and non-plant-based. Cannabis, a plant-based narcotic, is an example of a substance prohibited for use in the health sector in Indonesia. However, some countries permit the use of narcotics, such as Thailand, which allows the use of cannabis for public health benefits. This research is normative research, also known as doctrinal legal research, which involves examining existing legal rules using secondary data from library legal research. The study shows that there are differences in the rule of law between Indonesia and Thailand. The Indonesian Narcotics Act expressly prohibits the use of cannabis narcotics in the medical field, while in Thailand, the use of narcotics is allowed for medical purposes under government-determined conditions. In Indonesia, the use of cannabis narcotics is subject to clear criminal sanctions as specified in the governing law. However, in the Netherlands, the government has legalized the use of cannabis for medical purposes.